Estratégia de enfrentamento da pandemia Covid-19, utilizando ferramentas digitais – uma pesquisa-ação, realizada na feira do teatro de Cascavel - PR - Zanini , Elaine de Oliveira (2022)
Family farming is the main responsible for the country's food supply and is directly linked to food security and the development of the place where it operates. Thus, this work had as general objective to propose a digital dissemination strategy through the development of a website for displaying the products sold by family farmers at the municipal fair. Regarding the methodology, this research is characterized as bibliographical, exploratory action research type, in relation to its results, it is a qualitative study Data collection took place through interviews with those involved with family farming in the municipality of Cascavel - PR and the application of questionnaires with family farmers and consumers at the municipal fair. The survey results identified several difficulties of family farmers at the municipal fair, and it can be said that the hypothesis of this study is true that family farmers need a new strategy to help in the sale of products, but are unable to carry it out, as there is a need for professional management with knowledge and time dedicated to this project so that this type of dissemination can provide positive results, which they are unable to do, as the responses to the questionnaires revealed limiting factors for the adoption of technologies, such as lack of knowledge and time. It is concluded that the COVID-19 pandemic had negative repercussions on the income of family farmers at the municipal fair, among other difficulties faced in the pandemic, they reported a significant drop in sales, reaching up to 70%, revealing that local strategies are needed to alleviate their negative effects and in this sense, the insertion of family farmers in digital markets can be a good strategy to face the pandemic and post-pandemic.